Rancang Bangun Alat Deteksi Sag Tegangan Menggunakan Sistem Data Logger - Arizal Maulana Pratama; Ferdian Ronilaya; Ajeng Bening Kusumaningtyas; Sapto Wibowo (Politeknik Negeri Malang, 2021)
-This research discusses the design and manufacture of a voltage sag detection device using a data logger system. Voltage sag detection device to detect the presence of voltage sag which is one of the power quality problems in industrial electrical systems. Voltage sag can cause disturbances in electronic components that are sensitive to changes in voltage values. In this device, the voltage sag is detected using a voltage sensor by reading the RMS voltage from the PLN 220V AC source, then it is converted into a digital signal. The digital signal is sent to the ESP32 module to be processed and outputs a voltage value which is then displayed on the LCD Display. The voltage value data collection is carried out every <10ms and the data taken is the voltage value <90% of the rms voltage. The data taken is then saved to a micro SD card and displayed on the LCD Display. Several tests were carried out to ensure the performance of the voltage sag detector as designed. By switching the 110 / 220VAC transformer connected to the voltage sensor for 10 seconds, 12 seconds and 17 seconds. Based on these tests, the voltage sag detector can read and store the voltage sag data when the voltage read is below 90% of the rms voltage.